Silicon technologies ion implantation and thermal treatment - Baudrant, Annie (ISTE ; Wiley, 2011)
The main purpose of this book is to remind new engineers in silicon foundry, the fundamental physical and chemical rules in major Front end treatments: oxidation, epitaxy, ion implantation and impurities diffusion.